SIMULASI SISTEM PENYIRAM TANAMAN HIAS MENGGUNAKAN KONTROL LOGIKA FUZZY BERBASIS INTERNET OF THINGS - Mahasinul Akhlak, Muhammad Lutfi; Saputra, Muhammad Andri; Putranto, Vincensius Indrawan; Ridho, Rasyid (STMIK BINA PATRIA, 2024)
Ornamental plants are a type of plant that is cultivated to provide additional artistic and aesthetic value to the surrounding environment. There are several things that must be considered in cultivating ornamental plants, one of which is watering. One technology that can help humans in watering ornamental plants automatically is the Internet of Things with data processing using Fuzzy logic. This study uses the ADDIE method (Analysis, Design, Development, Implementation, Evaluation) and research instruments using cysco packet tracers, Blynk, Matlab, Arduino IDE, Proteus and MakeProto software. This system uses temperature and soil moisture sensors that function as detectors of soil moisture and air temperature then send instructions to Arduino to turn on the relay driver so that the pump can automatically flush water according to soil needs. Temperature and soil moisture sensor data is processed using fuzzy logic as input and produces output in the form of pump status, namely the pump is on or off. After being tested on matlab software using rule viewer and simulink and arduino IDE software which is run using proteus software, it produces the same output value if the input value is also the same. So it can be concluded that the Simulation of Ornamental Plant Watering System with IoT-based Fuzzy logic control can run according to the research objectives. This system also offers an efficient and accurate monitoring solution compared to manual methods, and works automatically without requiring human intervention.Keywords: Internet of Things; ADDIE, Fuzzy, Arduino, Matlab